A comprehensive review of the literature on Green Human Resource Management: Bibliometric analysis - U.Amaleshwari, R.Masilamani, (European Economic Letters (EEL), 2024)
Green Human Resource Management (Green HRM) is an approach that emphasizes the integration of environmental sustainability into human resource management practices. It involves promoting environmentally friendly policies and practices within an organization while also considering the well-being of employees. The concept of Green HRM acknowledges the role of HR in fostering a sustainable work environment and aligning organizational goals with environmental responsibility. The concept initiatives such as promoting energy efficiency, waste reduction, and sustainable sourcing, as well as incorporating green practices into talent management, employee engagement, and training programs. The view on Green HRM has generally been positive, with many organizations recognizing the importance of environmental sustainability in today's business landscape. However, it's important to note that attitudes and perspectives on Green HRM may vary based on industry, geographical location, and organizational culture. Additionally, developments and changes may have occurred since my last update in January 2022, so it's advisable to check more recent sources for the latest information on the current view about Green HRM. The growing emphasis on environmental protection has given rise to a novel research paradigm within the realm of human resource management (HRM). This bibliometric analysis scrutinized 70 documents related to GHRM concept. The study aimed to analyse the keywords, definition and description of green hrm, future study, journal publications, global distribution, prominent journals, and prevailing sectors in the field of GHRM. Furthermore, this study summarizes the major developments in this research domain and suggests research gaps and possible future directions.